Economic dependence of forest fringe communities on threatened and near-threatened medicinal trees of Madhya Pradesh - the largest forest cover state of central India - Patil, Abhay Kumar; Kumar, Vijay; Chaudhry, Pradeep (Ecological Questions, 2021)
People have a free access to the Non timber forest produce (NTFP) in the State of Madhya Pradesh, India barring only a few NTFP which are monopolized by the state for collection and trade. Because of such free access tenure, people and the policy makers have little appreciation for the provisional ecosystem services emanating from the state’s forests. Hence, a research study was conducted in Madhya Pradesh state of India during 2014-2015.This paper evaluates the dependence of the forest fringe communities on the already Threatened and Near-threatened Medicinal Tree resources (TNMTs) in the forests of the state for their health and livelihood requirements.This study was conducted in all the six eco-regions of the state after selecting the most forested divisions and purposely selected forest compartments and socio-economic surveys were conducted in the villages adjoining these forest compartments. The TNMTs of these compartments were fully enumerated in the selected compartments and their physical conditions were recorded. Focus group discussions and household surveys were conducted to study the dependence of forest fringe communities on TNMTs in the adjoining forests. The results show that contribution of direct forest income to the total annual household income was found to vary from 29.35% to 69.48% in forest divisions located in all the six eco-regions of the state. In all the six eco-regions, the percentage of households found to be dependent on forests for some or the other benefits ranged from 96% to 100%.  Almost all the TNMTs encountered during this survey were found facing threat of local extinction due to poor regeneration and many other factors at most of the forest sites. The authors have suggested some corrective measures for sustainable management of forest resources for the benefit of forest fringe community in the article.